DINAMIKA PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN: ANALISIS NILAI PERUSAHAAN MELALUI PERSPEKTIF MANAJEMEN LABA - Evi Maria Devi; Nur Aisyah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of profitability, liquidity, and firm size on firm value, with earnings management serving as a moderating variable. The research was conducted on manufacturing companies in the food and beverage sub sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A purposive sampling method was applied, resulting in a total sample of 17 companies that met the established research criteria. Data analysis was carried out using SPSS version 20, incorporating classical assumption testing and moderated regression analysis. The hypothesis testing methods included multiple linear regression, along with the t-test, F-test, and the coefficient of determination (R²). The findings demonstrate that profitability has a positive and significant effect on firm value. Conversely, liquidity and firm size do not show a significant impact on firm value. Furthermore, the results indicate that earnings management moderates the relationship between profitability and firm value. However, earnings management does not moderate the relationship between liquidity or firm size and firm value.